A Case of Initially Undiagnosed Chikungunya Arthritis Developing into Chronic Phase in a Nonendemic Area - Pui Shan Julia Chan; Moon Ho Leung (Case Reports in Medicine)
This case report described a 40-year-old lady presented with fever, headache, arthralgia, myalgia, and impaired liver function after returning from the Philippines. Chikungunya virus (CHIKV) and dengue serology were negative. Eight weeks after initial presentation, she experienced inflammatory polyarthritis mimic rheumatoid arthritis. This time CHIKV-IgM was detected, together with a >4-fold rise of CHIKV-polyvalent-antibody titre. The first CHIKV-IgM negative sample was reexamined and was CHIKV-PCR positive. CHIKV infection was confirmed and diagnosis of CHIKV-related arthritis was made. A quarter of CHIKV infected individuals develop post-CHIKV rheumatisms that affect quality of life and may need treatment with Disease Modifying Antirheumatic Drugs. This case highlights the importance of considering CHIKV infection in patients present with symmetrical polyarthritis particularly after travel to endemic regions. Testing of both CHIKV acute and convalescent-phase serum for CHIKV antibodies and PCR is recommended in suspicious case.